The relationship between economic growth and inequality: evidence from the age of market liberalism - Gerardo Angeles-Castro (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
Based on panel data we find that the inequality-growth relationship follows an ordinary-U curve during the period 1970-1998, in which inequality first decreases and then increases with economic growth. We also find some evidence that the increasing pattern of inequality may reverse at higher levels of income. The time-series approach complements the analysis and reveals that a substantial group of countries capture a minimum turning point in the 1980s on average and it is found to occur earlier for developed economies compare to developing ones; only a few countries reverse inequality in a latter stage and display a maximum turning point during the late 1990s; these countries are associated with a high governance indicator and moderate expansion of trade and FDI. Hence, during the era of market openness the inequalitygrowth relationship changed and became positive, although it is likely that income distribution improves with economic growth at a latter stage; the implication of this is that this relationship can be described in period cycles.
Keywords: C23; C22; O15; 330; Economic liberalisation; Income distribution; Economic Growth; Dynamic Panel Data Models; Time Series Analysis